The Effects of Team-Based Learning (TBL) Education on Critical Thinking, Interpersonal Relationships, Self-Leadership and Academic Major Satisfaction - Lee, Suk-Young; Kang, Seung-Ju (Journal of Engineering Education Transformations, 2021)
This study was conducted to develop and evaluate the effects of the Team-Based Learning (TBL) education program, in the college course â€œTheory of Nursing Process, on critical thinking, interpersonal relationships, self-leadership and academic major satisfaction among nursing college students. The methodology used in this research is an experimental study of a group of pretest-posttest design, which was designed to check for differences before and after the intervention through the TBL education program to the treatment group. The participants in this study are second-grade nursing students at H University in J city, South Korea. From March 24, 2019, to June 15, 2019, the TBL education program was applied to â€œTheory of Nursing Processâ€ classes for a total of 10 weeks, 2 hours per week. The collected data were analyzed with descriptive statistics and paired t-tests using the SPSS WIN 21.0 Program. The effects of the TBL educational program on critical thinking ability, interpersonal relationships, self-leadership and satisfaction toward the nursing major were statistically significant, as follows: critical thinking ability(t=-4.09, p = .000), interpersonal relationship(t=-3.35, p = .001), self-leadership (t=- 3.48, p = .001) and major satisfaction(t=-2.47, p = .016). The above findings confirm that the application of team-based learning in nursing education can positively affect critical thinking, interpersonal relationships and self-leadership among nursing students, and increase academic major satisfaction. After the intervention of the TBL training program, a correlation between variables was found. Critical thinking and interpersonal skills (r = 382, p = .002), critical thinking and self-leadership (r = .360, p = .003), critical thinking and major satisfaction (r = 534, p = .000 ), Interpersonal Skills and Self Leadership (r = .861, p = .000), Interpersonal Skills and Main Satisfaction (r = .627, p = .000), Self Leadership and Main Satisfaction (r = .654, p = .000) showed a significant positive correlation. he results above confirm that applying teambased learning to nursing education can have a positive impact on critical thinking, interpersonal, and self-leadership among nursing students and increase academic satisfaction. It can be seen that critical satisfaction correlates with critical thinking, interpersonal ability, and self-leadership.